Implementing Project Based Learning Policy Through Grindle's Framework: A Case Study of Success Factors and Student Outcomes in an Indonesian Elementary School - Dendy Rossa Triyantara; Budi Purwoko (Papanda Publisher, 2026)
Project Based Learning (PjBL) represents a strategic approach for developing 21st-century competencies, yet its implementation success depends heavily on systematic policy execution. This research examines PjBL policy implementation at Ciputra Elementary School through Grindle's theoretical framework, encompassing policy content and implementation context dimensions. A qualitative case study was conducted involving 62 teachers, 240 students (grades 4-6), and 12 management staff during the 2024/2025 academic year. Data were collected through classroom observations, in-depth interviews, focus group discussions, and document analysis, then analyzed using Miles et al.'s interactive model with triangulation for validity. Policy content dimension achieved high success rates: program implementers (90%), benefits (88%), affected interests (85%), decision-making location (82%), degree of change (78%), and resources deployed (75%). Implementation context showed institutional characteristics (87%), implementer compliance and responsiveness (86%), and stakeholder dynamics (83%). Student learning outcomes demonstrated substantial improvements: collaboration (+28%), creativity (+24%), critical thinking (+24%), conceptual understanding (+20%), and communication (+20%), with large effect sizes (Cohen's d = 1.15-1.52). Findings validate Grindle's framework applicability in educational innovation contexts, demonstrating that implementation success emerges from the interplay between teacher capacity, organizational support, adequate resources, and stakeholder alignment. The research provides theoretical contributions to policy implementation literature and practical implications for schools adopting project-based approaches.